Experimental verification of the effectiveness of methods of training the head of a vocal ensemble - Манлі, Ху (Pedagogy of Higher and Secondary Education, 2016)
Hu Manley. Experimental verification of the effectiveness of methods of training the head of a vocal ensemble. The article reveals the effectiveness of the methodology proposed for professional training of music teacher as a guide of a vocal ensemble in higher musical and pedagogical education in Ukraine and China. The article presents peculiarities of experimental verification of the effectiveness of methods of training the guide of a vocal ensemble. At ascertaining experiment, we have found that the modern musical and pedagogical education does not ensure proper conditions for the task. On the basis of theoretical study and analysis of the problem we have developed and scientifically proved the methodology for effective training of future guide of a vocal ensemble in noted direction. At the forming experiment, we have used a variety of methods, namely, testing, surveys, research interviews, observations, modeling of practical situations, the method of outline adaptation of musical compositions, the method of simulations of rehearsals with the vocal ensemble, the method of network planning, modeling method of teaching and rehearsals, analysis of the results of practice, statistical measurement. The proposed method involves directing teaching and learning process and the implementation of the training course «Methods of work with the vocal ensemble» by the teachers of higher musical and pedagogical education and mastering necessary educational information and ways of realization of musical and pedagogical activity by future heads of vocal ensembles. This method is shown in theoretical propositions and conclusions. Experimental work covers several stages to consistently achieve the objectives we have for the preparation and analysis of the results of forming experiment. The choice of methods involved in experimental research is associated with the need to obtain reliable data that indicate the dynamics of change, and effectiveness of system of higher musical amd pedagogical education in Ukraine and China. The students have got theoretical and methodological experience, gained the necessary professional knowledge, mastered methods of preparations, rehearsal and concert activities associated with vocal development of pupils and their musical and aesthetic development. Prospects for further research is in using of interactive technologies during the vocal development of students of vocal ensemble.